Islamisasi di Nusantara: Pendekatan Sufistik dalam Dakwah Islam - Alim, Syahirul (Faculty of Dakwah and Communication, UIN Syarif Hidayatullah Jakarta, 2024)
Islamization in the Archipelago became a unique process of Islamic conversion, different from the process of Islamization in other regions in the Middle East. In addition to the role of traders from Arabia, China or India, Islamization in the archipelago was initiated by Sufi masters who sailed with the traders to the archipelago. Through a Sufistic approach, people were attracted to Islam because this religion provides a space for freedom, breaking down the barriers of primordialism and social elitism. Through cognitive liberation, Sufi masters opened the horizons of understanding Islamic teachings without contradicting them with local traditions. Sufi masters are potential figures in social movements in the entire process of Islamization in the archipelago. Through the cognitive liberation approach, Islamic preaching encourages more awareness of Islamic identity to fight ignorance, social injustice, and also colonialism. Islamization with a Sufistic model, ultimately shapes the intellectual-religious perspective of Muslim communities in Indonesia which tends to be moderate and inclusive.